ISOLATION AND CHARACTERIZATION of BACTERIA DEGRADING - Hadija Enryani Ismail (Marina Chimica Acta, 2016)
The aim of this study was to obtain bacterial isolates originating from Port Paotere waters capable of degrading pyrene compound. From the results of the isolation and molecular characterization of the 16S rRNA gene was obtained 3 types of bacteria is Alcaligenes faecalis to isolate A, Sphingobacterium sp. to isolate B, Bacillus Cereus to isolate C. BLAST results for the third isolates achieve a high degree of similarity genus, reaching 99%.Keywords: Polycyclic Aromatic Hydrocarbons (HAP), pyrene, isolation of bacteria, biodegradation